Habitat Characteristics of Polar Bear Terrestrial Maternal Den Sites in Northern Alaska - Durner, George M.; Amstrup, Steven C.; Fischbach, Anthony S. (ARCTIC, 2003)
Polar bears (Ursus maritimus) give birth to and nurture their young in dens of ice and snow. During 1999-2001, we measured the structure of 22 dens on the coastal plain of northern Alaska after polar bear families had evacuated their dens in the spring. During the summers of 2001 and 2002, we revisited the sites of 42 maternal and autumn exploratory dens and recorded characteristics of the under-snow habitat. The structure of polar bear snow dens was highly variable. Most were simple chambers with a single entrance/egress tunnel. Others had multiple chambers and additional tunnels. Thickness of snow above and below dens was highly variable, but most dens were overlain by less than 1 m of snow. Dens were located on, or associated with, pronounced landscape features (primarily coastal and river banks, but also a lake shore and an abandoned oil field gravel pad) that are readily distinguished from the surrounding terrain in summer and catch snow in early winter. Although easily identified, den landforms in northern Alaska were more subtle than den habitats in many other parts of the Arctic. The structure of polar bear dens in Alaska was strikingly similar to that of dens elsewhere and has remained largely unchanged in northern Alaska for more than 25 years. Knowledge of den structure and site characteristics will allow resource managers to identify habitats with the greatest probability of holding dens. This information may assist resource managers in preventing negative impacts of mineral exploration and extraction on polar bears. Les ourses polaires (Ursus maritimus) donnent naissance et nourrissent leurs petits dans des tanières de glace et de neige. De 1999 à 2001, on a mesuré la structure de 22 tanières situées sur la plaine côtière de l'Alaska septentrional après que les familles d'ours polaires eurent évacué leurs tanières au printemps. Au cours des étés de 2001 et de 2002, on s'est à nouveau rendus sur les sites de 42 tanières de mise bas et d'exploration automnale et on a mesuré les caractéristiques de ...